Features of fashion designers' training in Ukrainian and European universities - Kyselova, K. (Theory and practice of design, 2016)
The article explores various approaches to study of formbuilding and mastering of design work niceties in Ukrainian and European higher education establishments training fashion design specialists. It discusses the differences in the admission requirements, approaches to specialization, set of studied disciplines, organization of the learning process and creative tasks at all training phases, starting from preparation courses to the level of master’s degree. The article unveils strategic advantages of formation of comprehensive attitude in the students to design work through gradual complication of tasks with compulsory yield of finished projects at all stages of study. It also characterizes ways for improvement of educational process in fashion design by means of splitting and narrowing of specializations as well as further individualization of creative tasks and their customization to actual requirements of modern society.